Dynamic Task Scheduling Based on Abelian Sandpile and Rotor-Router Models - Hayk E. Nahapetyan; Suren S. Poghosyan (Изд-во НАН РА)
This study is dedicated to the possible usage of self-organized criticality models in large-scale computing systems for load balancing and energy-awareness. Methods and software tools aimed at modeling and visualization of dynamic tasks scheduling in virtual distributed systems constructed over sandpile and rotor-router models, are also presented.
Keywords: Mathematics; Algorithm